Cowboy classics : the roots of the American western in the epic tradition - Day, Kirsten, 1969- (Screening antiquity., 2016)
Compares the ancient epic and the American Western as parallel cultural narratives. Cowboy Classics looks at the remarkably intimate connection between Westerns and Greek and Roman epics, each of which focuses on a mythic-historical period from the past where our societal notions of what constitutes heroism, masculinity and honour were first forged. Through her insightful analysis of Red River, High Noon, Shane, The Searchers and The Man Who Shot Liberty Valance, Kirsten Day illustrates the parallels between these seemingly disparate yet closely related genres, allowing us to see each through a new lens while gaining insight into the persistence of these concepts in our world today. Key Features. Discusses the recent scholarly interest in classical representations in popular culture Looks at how both Greco-Roman epic and Western film in general help to define foundational ideologies for their respective cultures Includes case studies of four films - Howard Hawks' Red River (1948), Fred Zinnemann's High Noon (1952), George Stevens' Shane (1953), and John Ford's The Searchers (1956) - which analyze specific affinities with the Homeric epics and Virgil's Aeneid Examines John Ford's The Man Who Shot Liberty Valance (1962) as an Oedipal drama, in relation to Greek and Roman epic